A comparison of teachers' attitudes to racial integration in schools in apartheid and post-apartheid South Africa - Steiner, Ruth (My University, 2014)
The aims o f this study were: l).To assess the attitudes of teachers at 16 English-medium high schools towards integrated schooling and to determine their perceived sources of stress. 2). To ascertain whether any changes in teacher attitudes had taken place between 1990 and 1996 at these schools. 3). To determine whether certain teacher or school variables were associated with teachers’ attitudes. 4). To investigate teachers’ perceptions o f the difficulties and benefits of school integration, and their suggestions with regard to facilitating the integration process. The opinions of 317 (white) teachers were obtained via a questionnaire. The results indicated that the teachers in this study strongly supported integrated schooling, although they acknowledged that problems do exist. While English speaking respondents were slightly more positive than were Afrikaans speaking respondents, the most significant variable influencing results was school type. Teachers at private (independent) schools were generally more positive than ivere teachers at government (public) schools, while teaching in the more integrated schools influenced both positive attitudes and greater sensitivity to multicultural issues. Higher teacher qualifications generally indicated increasingly positive attitudes, while attitudes were not found to be significantly influenced by either age or sex. Teachers who had previously attended courses were more aware of difficulties and endorsed the need for special training. The overall perceived stress level of the teachers was not acute, indicating that they do cope. The longitudinal comparison between 1990 and 1996, indicated a highly significant movement towards more positive attitudes to integration in all groups except the more integrated private schools which had already expressed highly positive views. The most nsnarkable positive shift occurred in the attitudes of Afrikaans speaking teachers. Although teacftar have become less anxious about perceived problems associated with integration, concern the inferior educational background of disadvantaged pupils has persisted.